2012
DOI: 10.4236/health.2012.49097
|View full text |Cite
|
Sign up to set email alerts
|

Association between head-and-neck cancers and active and passive cigarette smoking

Abstract: Although there have been many reports on the toxicity of tobacco smoke, fewer studies have reported the relationship between the smoke and carcinogenesis of head-and-neck cancers. It is assumed that direct stimulations due to tobacco smoke, such as chemical and mechanical stimulations, strongly influence the epithelium of the nasal cavity, paranasal sinuses, pharynx, and larynx. We investigated the influence of active and passive cigarette smoking on head-and-neck cancers. The subjects were 283 head-and-neck c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Previous HNSCC studies have reported varying rates of smoking at diagnosis, ranging from 26.4% to 56% . Smoking rates tend to be heterogeneous across head and neck subsites, with the larynx having the higher rates and a greater likelihood of being associated with smoking . Our study confirms this.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous HNSCC studies have reported varying rates of smoking at diagnosis, ranging from 26.4% to 56% . Smoking rates tend to be heterogeneous across head and neck subsites, with the larynx having the higher rates and a greater likelihood of being associated with smoking . Our study confirms this.…”
Section: Discussionsupporting
confidence: 86%
“…9 Smoking rates tend to be heterogeneous across head and neck subsites, with the larynx having the higher rates and a greater likelihood of being associated with smoking. 9,36,37 Our study confirms this. We found that patients with laryngeal cancer had a significantly higher smoking rate than patients with cancer of the other subsites.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, it is considered a risk factor of oral cancer in both active and passive smokers, influenced by the duration and dose of exposure to it. A previous study by Kushihashi et al (2012), 3 assessed the impact of the number of cigarettes smoked per day and the duration of smoking among active smokers or that of cigarette exposure among passive smokers on the occurrence of head and neck cancer. The study argued that smoking plays a significant role in the development of squamous cell carcinoma (p = 0.0338).…”
Section: Discussionmentioning
confidence: 99%
“…These include cancer of the oral cavity, pharynx and larynx, in addition to lung cancer. 3 The process of carcinogenesis is a somatic event thought to be caused by accumulative genetic and epigenetic changes affecting the normal molecular control settings in cell proliferation. These genetic changes can subsequently deactivate the tumor suppressor gene, thereby triggering tumor formation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Worryingly, the population of passive smokers is reportedly outstripping that of active ones. 2 In fact, both categories of smoker run the risk of developing cancer since cigarettes contain various carcinogenic substances, such as polycyclic aromatic hydrocarbons (PAHs) 3 , and Nitrosamines consisting of 4-(methylnitrosamino) -1-(3-pyridyl) -1-butanone (NNK) and N'-nitrosonornicotine (NNN). Each substance is known to have carcinogenic properties in relation to human beings.…”
Section: Introductionmentioning
confidence: 99%